The Influence of Biodiversity Teaching Materials Based on Ethnobiological Studies on Students' Scientific Reasoning - Idah Hamidah; Lesy Luzyawati; Rani Suryani (Mangifera Edu, 2023)
The scientific reasoning of students at MA Negeri 1 Indramayu is in the moderate category. Biodiversity teaching materials based on ethnobiological studies have never been applied. This study aims to determine the influence of biodiversity teaching materials based on ethnobiological studies on the scientific reasoning of students at MA Negeri 1 Indramayu. The research method used, that is, quantitative. The design of this study, namely true experimental design with the type of posttest only control design. The population of this study, namely class X MA Negeri 1 Indramayu students consisting of 3 classes with a sample of class X MIPA 1 totaling 30 students as an experimental group and class X MIPA 3 totaling 29 students as a control group. The sampling technique uses cluster random sampling. The instruments used are in the form of tests and questionnaires. Data analysis using normality test, homogeneity test, t-test and likert scale. The results showed that the average scientific reasoning of the experimental group students was higher compared to the control group. Based on the hypothesis test value (thitung = 3.392 > ttabel 2.2002) so that H0 is rejected and Ha is accepted, that is to say, there is a significant influence of biodiversity teaching materials based on ethnobiological studies on the scientific reasoning of students in MA Negeri 1 Indramayu. Students' scientific reasoning is in the high category with a percentage of 66.72%.